Quantifying the pattern of optic tract degeneration in human hemianopia. - Millington, R; Yasuda, C; Jindahra, P; Jenkinson, M; Barbur, J; Kennard, C; Cendes, F; Plant, G; Bridge, H (2014)
BACKGROUND: The existence of transsynaptic retrograde degeneration (TRD) in the human visual system has been established, however the dependence of TRD on different factors such as lesion location, size and manner of lesion acquisition has yet to be quantified. METHODS: We obtained T1-weighted structural and diffusion-weighted images for 26 patients with adult-acquired or congenital hemianopia and 12 age-matched controls. The optic tract (OT) was defined and measured in the structural and diffusion-weighted images, and degeneration assessed by comparing the integrity of tracts in the lesioned and in the undamaged hemisphere. RESULTS: OT degeneration was found in all patients with established lesions, regardless of lesion location. In patients with acquired lesions, the larger the initial lesion, the greater is the resulting TRD. However, this was not the case for congenital patients, who generally showed greater degeneration than would be predicted by lesion size. A better predictor of TRD was the size of the visual field deficit, which was correlated with degeneration across all patients. Interestingly, although diffusion-weighted imaging (DWI) is more frequently used to examine white matter tracts, in this study the T1-weighted scans gave a better indication of the extent of tract degeneration. CONCLUSIONS: We conclude that TRD of the OT occurs in acquired and congenital hemianopia, is correlated with visual field loss, and is most severe in congenital cases. Understanding the pattern of TRD may help to predict effects of any visual rehabilitation training.